Impact of ferroptosis-related risk genes on macrophage M1/M2 polarization and prognosis in glioblastoma - Xu, Xin; Zhang, Yue; Liao, Chenlong; Zhou, Han; Wu, Yiwei; Zhang, Wenchuan (Frontiers in Cellular Neuroscience, 2024)
Objective: To explore the effect impact of ferroptosis on macrophage polarization and patient prognosis in glioblastoma.We screened ferroptosis-related risk from the public datasets of primary and recurrent glioblastoma, combined with reported ferroptosis genes, calculated the risk genes among the ferroptosis-related genes using the LASSO Cox regression model, and investigated the relationship between these ferroptosis-related risk genes in the tumor and the spectrum of infiltrating M1/M2 macrophages. Macrophages were analyzed using the CIBERSORTx deconvolution algorithm. Samples from The Cancer Genome Atlas (TCGA), Chinese Glioma Genome Atlas (CGGA) and a single-cell RNA sequencing dataset (GSE84465) were included. The expression levels of ferroptosisrelated risk genes and molecular markers of M1 and M2 macrophages were detected by qPCR and western blot.Results: A total of fourteen ferroptosis-related risk genes were obtained and the patients' risk scores were calculated. Compared with patients in the low-risk group, patients in the high-risk group had worse prognosis. The M1/M2 macrophage ratio and risk score were negatively correlated, indicating that the tumor microenvironment of glioblastoma in the high-risk group contained more M2 than M1 macrophages. In the single-cell RNA sequencing dataset, the risk score of ferroptosis-related genes in tumor cells was positively correlated with the proportion of high M2 macrophages. The expression of eight ferroptosis-related risk genes was increased in glioblastoma cell, which promoted the polarization of M1 macrophages to M2.We investigated the fourteen ferroptosis-related risk genes in glioblastoma for the first time, and clarified the impact of ferroptosis-related risk genes on M1/M2 macrophage polarization and patient prognosis.